Nested Polymerase Chain Reaction (Nested-PCR) As A Diagnostic Technique for Intestinal Helminth Infection - Reqgi First Trasia (Universitas Al Azhar Indonesia, 2020)
Abstract - Worm infections are still a health problem in the world, involving Indonesia. This disease generally rarely causes death, it has a detrimental impact on society such as malnutrition, anemia, productivity declining, and inhibits physical growth and intelligence in children. Efforts to support the intestinal helminth infection elimination program must be supported by proper diagnosis so that it can be continued with appropriate treatment and as a guideline for determining further policy. Microscopic examination is currently still the most commonly used method but has a limitation, especially less sensitive if in conditions of low infection. Molecular diagnoses suc [1]h as PCR can provide an alternative in providing a more sensitive and specific diagnosis of intestinal helminth infection.Keywords - Diagnosis, Intestinal helminth infections, Polymerase Chain Reaction